A sneak peak into the neurologic complications associated with H1N1 influenza - Chaluvadi, Siresha; Agadi, Satish; Riviello, James J. (Journal of Pediatric Neurology, 2011)
The numbers of hospitalizations, multiorgan complications, and deaths continued to rise during the H1N1 influenza pandemic. Although there are several reports of H1N1 influenza associated neurologic complications in all ages, there is no clear suggestion that the 2009 influenza A (H1N1) virus is associated with a disproportionate amount of neurologic illness beyond that observed with seasonal influenza. We describe the serious neurologic complications of children hospitalized with H1N1 influenza in Houston, Texas during the 2009 season. We retrospectively studied five hospitalized children with neurological complications who were polymerase chain reaction positive for the H1N1 virus. In these five children, two had stroke (ischemic and/or hemorrhagic), two had seizures, and three had encephalopathic features. Regarding the outcome, improvement in neurological function occurred in four and one child died. These five children with neurologic complications represented 21% of the children with H1N1 influenza admitted to the pediatric intensive care unit.
Keywords: H1N1; seizures; encephalopathy; stroke